PENDUGAAN DAYA TAMPUNG RUSA LIAR (Cervus timorensis) DI PADANG RUMPUT MAR TAMAN NASIONAL WASUR MERAUKE - Tjahyono Hariadi, Bambang; Sraun, Thimotius (Pastura; Vol 3 No 1, 2014)
The objective of this experiment was to know carrying capacity of rusa deer (Cervus timorensisi) at Mar, Wasur National Park Merauke district. The data collected were spesies of grasses, production each species and carrying capacity. The results showed species of grasses were Cynadon dactylon, Imperata cylindrica and Phragmites karka. Mar was dominated by Cynadon dactylon. The production of Cynodon dactylon was 2.183 kg/ha. The carryng capacity of rusa deer was 0.5 ha/head/year.
Keywords: carryng capacity, rusa deer, savannah, national park